An approach to the Contextual Design methodology in the context of Information Science - Machado, Luís Miguel Oliveira (2019)
Based on an operative definition of Information Science (IS) as a study of the mediation aspects of the phenomena: data, information, knowledge and message, and their implementation in the cultural domain, the potential of Contextual Design (CD) as a methodology for the development of optimized interfaces between information resources and users is analyzed. The goals are (i) to identify papers that address or make use of the CD methodology in databases related to IS; (ii) to describe the approaches to the concept of CD in those papers; (iii) to point out the potentials and limitations of this methodology. We draw an exploratory / descriptive study based on a systematic review and categorical analysis. Eight papers were retrieved, which may act as a potential indicator of the reduced use of this methodology in the IS area. Furthermore, its application is essentially practical. Although the limitation of non-involvement of users throughout all the design process is pointed out, the CD methodology shows the ability to collect implicit information through user activities and the possibility of shared systematization of complex data. These characteristics make CD a potential value for the development of appropriate interfaces between information resources and their users.